2021
DOI: 10.1038/s41434-021-00251-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction of X-CGD patient HSPCs by targeted CYBB cDNA insertion using CRISPR/Cas9 with 53BP1 inhibition for enhanced homology-directed repair

Abstract: X-linked chronic granulomatous disease is an immunodeficiency characterized by defective production of microbicidal reactive oxygen species (ROS) by phagocytes. Causative mutations occur throughout the 13 exons and splice sites of the CYBB gene, resulting in loss of gp91 phox protein. Here we report gene correction by homology-directed repair in patient hematopoietic stem/progenitor cells (HSPCs) using CRISPR/Cas9 for targeted insertion of CYBB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 77 publications
(135 reference statements)
3
46
0
Order By: Relevance
“…41,42 In the same direction, 53BP1 inhibition facilitates HDR in human HSPCs. 43,44 Other groups have reported the use of SR-1 molecule as an HDR pathway enhancer in TALEN and CRISPR/Cas9-mediated editing systems. 45 Aside from small molecules, it has been recently reported that inhibition of p53 increases the rate of HDR.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In the same direction, 53BP1 inhibition facilitates HDR in human HSPCs. 43,44 Other groups have reported the use of SR-1 molecule as an HDR pathway enhancer in TALEN and CRISPR/Cas9-mediated editing systems. 45 Aside from small molecules, it has been recently reported that inhibition of p53 increases the rate of HDR.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is gene editing with CD40LG replacement by HDR where the inclusion of the 3′ UTR is essential to ensure high gene expression levels ( Hubbard et al, 2016 ; Kuo et al, 2018 ). Studies have also shown that retaining intron one or the terminal intron in the cDNA can contribute positively to efficient expression levels ( Gray et al, 2021 ; Sweeney et al, 2021 ).…”
Section: Towards a Curative Crispr/cas9-based Gene Editing Approach F...mentioning
confidence: 99%
“… Targeted cell/model(s) Linked-disease(s) Applied CRISPR/Cas system Delivery system Edit/Alternation Reference HEK 293 Lung adenocarcinoma Cas9 system using CBh promoter to drive SpCas9, and U6 promoter to drive sgRNA Plasmid transfection Chromosomal rearrangement, including CD74-ROS1 translocation and the EML4-ALK and KIF5B-RET inversion events. [ 22 ] 5637 and T24 Bladder cancer Cas9 system CMV promoter to drive hCas9, and T7 promoter to drive sgRNA Plasmid transfection Down regulation of UCA1 gene [97] C57BL/Apcfl/fl, KrasG12D/+, and Trp53Δ/Δ mice Colorectal cancer Cas9 system using EFS promoter to drive Cas9 and U6 to drive sgRNA Lentiviral Suppression of Apc and Trp53 genes in colon epithelial cells [99] iPSC and fibroblasts β-thalassemia PiggyBac Cas9 expression vector Plasmid transfection HBB mutations correction without leaving any genetic footprint in patient-derived iPSC [132] CD34+ HSPCs X-linked chronic granulomatous disease CRISPR-SpCas9 RNP complexes Transfection Regulated expression of cDNA by the endogenous CYBB promoter for functional correction of patient cells [112] hiPSC FTDP-17 dCasRx system using EFS promoter to drive Cas13d, and U6 promoter to drive multiple guides AAV Induce exon exclusion to alleviate dysregulation of 4R/3R tau ratios at MAPT exon 10 [58] Fibroblast cells derived from an HD patient HD Specific allele-selective CRISPR/Cas9 system based on PAM-altering SNPs, with an EFS promoter to drive SpCas9, and a U6 promoter for expression of a dual-gRNA cassette Plasmid transfection Excise of the spanning promoter region at the mutated HTT gene with complete inactivation of the mutant allele without impacting the normal allele. [105] Note: iPSCs: human induced pluripotent stem cells, HBB: Hemoglobin subunit beta, piggyBac: (PB) is a transposon-based vector system.…”
Section: Insights Of Crispr-cas Systems As a Therapeuticmentioning
confidence: 99%